Eterni, fanciulli, alati: neotenia e leggerezza di classici angelici della letteratura per l’infanzia - Terrusi, Marcella (Studi sulla Formazione/Open Journal of Education, 2017)
Children’s literature is rich in carachters that share a common light and winged destiny. Between them classic icons as Peter Pan, The Little Prince, Cosimo Pio-vasco di Rondò, Mary Poppins, Nils Holgersson, Viperetta. Referring to the con-cept of neotenia and the junghian archetype of Puer Aeternus the essay proposes a reflection about symbols and metaphors of childhood and lightness as combined in those classics. The neverending dialectic among Puer and Senex, the perspec-tive of the Lightness as lirical quality are the keywords of this work.